Journal for the Study of Antisemitism : Contemporary Antisemitism and Racism in the Shadow of the Holocaust (Special Issue) - Stoegner, Karin; Bechter, Nicolas; Klaff, Lesley; Spencer, Philip; Stoegner, Karin; Bechter, Nicolas; Klaff, Lesley; Spencer, Philip (Academic Studies Press, 2021)
This Special Issue of the Journal for the Study of Antisemitism contains a collection of papers that were presented at the International Conference (3z(BContemporary Antisemitism and Racism in the Shadow of the Holocaust(3y$1 (Bthe midterm conference of the Research Network on Ethnic Relations, Racism and Antisemitism within the European Sociological Association. The network was set up over a decade ago with the aim of addressing what was felt to be a serious gap in contemporary social theory, the continuing and indeed growing presence of antisemitism and its connection to other racisms.s
Knowledge Unlatched
English
Keywords: Religious groups: social & cultural aspects; Religious intolerance, persecution & conflict; Social Science; Jewish Studies; Religion; Religious Intolerance, Persecution & Conflict